Preservación paisajística en la interfase natural-urbana de ciudades turísticas de montaña: Bariloche (Río Negro, Argentina) y localidades del Lago Tahoe, (California, EE. UU) - Rodríguez, Norberto Javier (2022)
The urban growth processes in mountain tourist cities, adjacent to attractive natural environments and with characteristics similar to Tahoe (USA) or Bariloche (Argentina), are related to processes defined as naturbanization. \nSince this landscape is the main attraction for tourism in these locations, its deterioration could be of concern not only in terms of environment and type of habitat for residents, but also for the economic sectors that depend on its appeal. For these reasons the thesis has focused on this research object. During the thesis, processes and logics that led to the formation of these urban border areas have been analyzed, based on their physical characteristics and habitability. Likewise, the expectations of the actors who take part in these spaces have been considered. In this way, there are expected to be contributions for better planning in these kinds of cities with an attractive natural environment, from a perspective that combines the vision of landscape ecology and territorial intelligence, promoting their future sustainability. For this purpose, physical environmental and social-spatial aspects have been considered (from quantitative and qualitative perspectives) in a systematized and comparative way at different scales. \nThe results have made it possible to infer the existence of risks and potentialities not considered properly in many cases for city planning, such as Bariloche, and with differential alternatives found in Tahoe, despite observing that they also have some risks and persistent conflicts. Based on this thesis, it is planned to continue acting to promote changes or micro-transformations in urbanization systems and territorial policies in natural or wild urban interface areas.